2019
DOI: 10.31220/osf.io/ugqk4
|View full text |Cite
|
Sign up to set email alerts
|

Danh Gia Hieu Qua Mot So Mo Hinh Nong Lam Ngu Ket Hop Tai Xa Dao Hon Tre, Kien Giang.

Abstract: Among the islands belonging to Kien Giang province, Hon Tre has geographical comparative advantages for ecological - economic models. This paper will focuse on studying and evaluating the pros and cons of natural and social economic conditions of the island that may afftect the ecological - economic models available in the Hon Tre island, Since then, characteristics of each ecological - economic models will be analysed. Finally, effective evaluation of these models based on economic, social and eviromwntal iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 1 publication
2
7
0
Order By: Relevance
“…More details can be found in Refs. [26,27]. We found that the resistivity ρ in the frustrated regime can go downward or upward at the transition temperature depending on D 1 [27], unlike in non-frustrated ferromagnets and antiferromagnnets shown earlier.…”
Section: B Frustrated J1 − J2 Model On a Simple Cubic Latticementioning
confidence: 45%
See 4 more Smart Citations
“…More details can be found in Refs. [26,27]. We found that the resistivity ρ in the frustrated regime can go downward or upward at the transition temperature depending on D 1 [27], unlike in non-frustrated ferromagnets and antiferromagnnets shown earlier.…”
Section: B Frustrated J1 − J2 Model On a Simple Cubic Latticementioning
confidence: 45%
“…The system is very unstable due to its large degeneracy. In the case of the Ising spin on the SC lattice treated here, we found that the first-order character of the phase transition is even stronger [27].…”
Section: B Frustrated J1 − J2 Model On a Simple Cubic Latticementioning
confidence: 62%
See 3 more Smart Citations